Adjustment of the GRACE Risk Score by Monocyte to High-Density Lipoprotein Ratio Improves Prediction of Adverse Cardiovascular Outcomes in Patients With Acute Coronary Syndrome Undergoing Percutaneous Coronary Intervention - Ma, Xiaoteng; Han, Kangning; Yang, Lixia; Shao, Qiaoyu; Li, Qiuxuan; Wang, Zhijian; Li, Yueping; Gao, Fei; Yang, Zhiqiang; Shi, Dongmei; Zhou, Yujie (Frontiers in Cardiovascular Medicine, 2022)
Background and Aims The monocyte to high-density lipoprotein cholesterol ratio (MHR), a novel marker for inflammation and lipid metabolism, has been demonstrated to be associated with poor prognosis in many patient populations. However, the prognostic influence of MHR in patients with acute coronary syndrome (ACS) undergoing percutaneous coronary intervention (PCI) is poorly understood. Here, we sought to investigate the relationship between MHR and adverse cardiovascular (CV) outcomes in such patients and determine whether MHR could improve the GRACE risk score based prognostic models. Methods and Results MHR was applied to 1,720 patients with ACS undergoing PCI who were admitted to our CV center from June 2016 to November 2017. These patients were stratified into three groups according to MHR tertiles. The relationship between MHR and the primary endpoint (overall death, non-fatal stroke, non-fatal myocardial infarction, or unplanned repeat revascularization) was examined by Cox proportional hazards regression analysis. During a median follow-up of 31 months, 353 patients had at least one primary endpoint event. Compared with those in the lowest MHR tertile, patients in the middle and highest tertiles [adjusted HR: 1.541 (95% CI: 1.152–2.060) and 1.800 (95%CI: 1.333–2.432), respectively], had a higher risk of the primary endpoint. The addition of MHR has an incremental effect on the predictive ability of the GRACE risk score for the primary endpoint (cNRI: 0.136, P < 0.001; IDI: 0.006, P < 0.001). Conclusion MHR was independently and significantly associated with adverse CV outcomes in ACS patients who underwent PCI and improved the predictive ability of the GRACE risk score based prognostic models. Registration Number http://www.chictr.org.cn/hvshowproject.aspx?id=21397; ChiCTR1800017417.